Stereotactic ablative radiotherapy treatment in multiple bilateral lung lesions: single-isocenter vs multiple-isocenter VMAT approach (Revista de Física Médica, 2020)
Stereotactic Body Radiation Therapy (SBRT) with volumetric-modulated arc-therapy is used since 2008 to treat limited lung disease.In this study, we compared single-isocenter vs multiple-isocenter approach in case of synchronous bilateral lung lesions treatment.Patients with bilateral lung disease were calculated in EclipseTM. For the first approach with one isocenter, two coplanar arcs were used. For the multiple-isocenter approach, four coplanar semi-arcs were used for each isocenter. All plans were normalized to at least 95% of the PTV receiving 100% of the prescribed dose and TG101’s constraints for the organs at risk (OAR) were adopted. Conformity indices, global maximum doses, maximum doses to any point 2cm or greater away from the PTV in any direction and doses at OARs (lung, spinal cord, heart, esophagus, trachea, ribs and skin) were recorded.No significant differences were observed in dosimetry indices and the OARs absolute doses were slightly better using two isocenters but OARs acceptance criteria was reached for all plans.The results show that both approaches are dosimetrically allowable. The use of single-isocenter technique can be recommended to obtain excellent plan quality with faster treatment time (single set-up) in bilateral lung lesions SABR.
Keywords: SBRT; VMAT; bilateral lung lesions; single-isocenter/multiple-isocenter